2004
DOI: 10.1007/s00500-004-0385-4
|View full text |Cite
|
Sign up to set email alerts
|

Using Factor Oracles for Machine Improvisation

Abstract: We describe variable markov models we have used for statistical learning of musical sequences, then we present the factor oracle, a data structure proposed by Crochemore & al for string matching. We show the relation between this structure and the previous models and indicate how it can be adapted for learning musical sequences and generating improvisations in a real-time context. Modeling musical sequencesStatistical modeling of musical sequences has been experimented since the very beginnings of musical info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 13 publications
0
61
0
1
Order By: Relevance
“…The Variable Markov Oracle (VMO) [25] is a suffix tree data structure that is derived from Factor Oracle (FO) [27,28] as well as Audio Oracle (AO) [29].…”
Section: The Variable Markov Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The Variable Markov Oracle (VMO) [25] is a suffix tree data structure that is derived from Factor Oracle (FO) [27,28] as well as Audio Oracle (AO) [29].…”
Section: The Variable Markov Modelmentioning
confidence: 99%
“…It has been employed mainly for optimal string matching algorithms, such as biosequence pattern matching. Assayag et al 2004 showed how the FO can be adapted to learn symbolic musical sequences and generate symbolic musical improvisations in real-time [28].…”
Section: The Variable Markov Modelmentioning
confidence: 99%
“…Afin de connaître la longueur du contexte commun entre deux évènements musicaux dans une séquence (Assayag, Dubnov, 2004) fait appel à la méthode présentée dans (Lefebvre, Lecroq, 2000) pour le calcul du vecteur lrs, linéaire en temps et en mémoire, en l'intégrant dans l'implémentation de la construction de l'oracle. La longueur de ce contexte correspond au paramètre c p introduit en 2.4.2.…”
Section: Parcours Guidé De La Mémoire : Suivre Des Enchaînements Satiunclassified
“…Assayag and Dubnov [18] have suggested using the Factor Oracle structure [19] for musical analysis and generation. The Factor Oracle is a state automata which, for a given sequence of length N, is able to represent the presence and location of repeated sub-sequences of variable length using a linear number of states (N + 1) and transitions (at most 2N − 1).…”
Section: A Musical Predictionmentioning
confidence: 99%